Calgary City of Animals (Calgary Institute for the Humanities, 2017)
How have our interactions with animals shaped Calgary? What can we do to ensure that humans and animals in the city continue to co-exist, and even flourish together? This wide-ranging book explores the ways that animals inhabit our city, our lives and our imaginations. Essays from animal historians, wildlife specialists, artists and writers address key issues such as human-wildlife interactions, livestock in the city, and animal performers at the Calgary Stampede. Contributions from some of Calgary's iconic arts institutions, including One Yellow Rabbit Performance Theatre, Decidedly Jazz Danceworks, and the Glenbow Museum, demonstrate how animals continue to be a source of inspiration and exploration for fashion, art, dance, and theatre. The full-colour volume is beautifully illustrated throughout with archival images, wildlife photography, documentary and production stills, and original artwork. Calgary: City of Animals is published in co-operation with the Calgary Institute for the Humanities.